(untitled) (Journal of Parents and Teachers, 2026)
Unfortunately, throughout history, schools have reinforced mechanisms of exclusion towards the poor. Schools take for granted requirements that are non-existent in poor communities and families and inaccessible to them: parental support, tranquillity, comfort, serenity. In addition to this, it selects and ranks students, separating the “winners” from the “losers”. In order to implement a new policy, it is necessary to build dialogue, adapt structures and programmes, professionalise the actors involved and ensure the strong involvement of the people concerned.